SOLID DISPERSION TECHNOLOGY, A CONTEMPORARY OVERVIEW ON A WELL ESTABLISHED TECHNIQUE - Younis, Mahmoud A. (Universal Journal of Pharmaceutical Research, 2017)
Solubility is a significant physicochemical parameter that affects the absorption, bioavailability and therapeutic effectiveness of any drug. Formulation development would fail if drug has a poor aqueous solubility. The low aqueous solubility of drug substances will lead to inadequate absorption and consequently, low bioavailability. Improvement of the aqueous solubility and dissolution rate of hydrophobic drugs remains one of the most difficult challenges in drug development process. Among various techniques used to improve poor aqueous solubility of drugs, solid dispersion technology has been extensively used in the literature and has become one of the well-established pharmaceutical procedures during formulation process. Although the technique seems to be “a part of the past”, literature tells us that it is still used and developed to suit current needs of pharmaceutical industry. This review article highlights recent advances in solid dispersion technology and its applications in contemporary pharmaceutical research. Peer Review History: Received 6 April 2017; Revised 14 May; Accepted 25 June, Available online 15 July 2017 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Dr. Mohammed Abdel-Wahab Sayed Abourehab , Umm Al-Qura University; Makkah Al-Mukarramah, Saudi Arabia, mohawahab2002@yahoo.com